Growth Response of Two Pepper (Piper nigrum L.) Stem Cuttings on Application of IBA (Indole Butyric Acid) and NAA (Naphthalene Acetic Acid) - Wulandari, Rizky; Hasanah, Yaya; Meiriani, Meiriani (Indonesian Journal of Agricultural Research, 2018)
Using fruit branch for pepper shrub propagation is one of alternatives for an efficient pepper multiplication which usually uses underlayer cuttings. This research is aimed at finding the growth response of two pepper (Piper nigrum L.) cuttings to the administration of IBA (Indole Butyric Acid) and NAA (Naphthalene Acetic Acid). This research was conducted at the greenhouse of the Faculty of Agriculture, University of Sumatera Utara, Medan (Â± 32 m above sea level), from April to August 2017 using a factorial randomized block design with 2 factors, pepper branch cuttings (primary branch cuttings and secondary branch cuttings) and the administration of IBA and NAA (0+0 ppm, 2500+0 ppm, 0+2500 ppm, 1500+1000 ppm, and 1000+1500 ppm). The results show that the emerging shoot rate in the secondary branch cuttings was significantly faster than in the primary branch cuttings, but the volume of root in the primary branch cuttings is significantly larger than in the secondary branch cuttings. There was no significant difference in the administration of IBA and NAA on all observed variables. The highest interaction of shoot length was found in the primary branch cuttings with the administration of IBA 1500 ppm + NAA 1000 ppm and the highest percentage of root and root volume was found in the primary branch cuttings with the administration of IBA 2500 ppm + NAA 0 ppm.